Comparison of penicillins (penicillin G and ampicillin) and cefazolin as a definitive therapy against penicillin-susceptible Staphylococcus aureus (PSSA) bacteremia in Japan: a retrospective cohort study. Issue 4 (April 2020) - Moriyama, Yuki; Ishikane, Masahiro; Mezaki, Kazuhisa; Ohmagari, Norio
Abstract: Objectives: Cefazolin has been the first-choice drug to treat penicillin-susceptible S taphylococcus aureus (PSSA) bacteremia, because oxacillin and nafcillin are not approved in Japan. Since February 2019, cefazolin supply is stagnant in Japan because of possible contamination issues. To look for cefazolin alternatives that can be used as a definitive therapy, we evaluated the usefulness of penicillins (penicillin G and ampicillin) against PSSA bacteremia. Methods: A retrospective cohort study of patients with methicillin-susceptible Staphylococcus aureus (MSSA) bacteremia was conducted between January 2012 and September 2017. MSSA was determined according to the Clinical and Laboratory Standards Institute guidelines. PSSA was defined as S. aureus with penicillin G minimum inhibitory concentration of ≤0.03 mg/L without using the zone edge test or blaZ PCR. Results: Of the 280 patients with MSSA bacteremia enrolled, and 138 (49.3%) was PSSA. Of the 44 patients who met the inclusion criteria, 11 were administered penicillins (penicillin G, n = 3 and ampicillin, n = 8) and 33 with cefazolin. Although the patients in the two groups had similar demographics, those in the penicillins group had significantly lower median Charlson score [interquartile range] than those in the cefazolin group (0[0–1] vs 1[0–4], p = 0.033). The two groups showed no significant differences regarding adverse events and bacteremia recurrence. None of the patients in the penicillins group died; however, 5 (15.2%) patients in the cefazolin group showed a 30-days mortality. Conclusion: Penicillins can be useful as a definitive therapy against PSSA bacteremia with stable condition, and they can be an alternative to cefazolin.